Challenges and Strategies in Teaching English for Young Learners Using Project-Based Learning Method - Jaya, Ketut Rivan Arya; Utami, I. G. A. Lokita Purnamika; Adnyayanti, Ni Luh Putu Era (STKIP AGAMA HINDU SINGARAJA, 2024)
This research describes a study regarding the challenges experienced by teachers when teaching English to young learners using the Project-Based Learning method in elementary schools as well as the strategies used by teachers to overcome the challenges they experience. The research subject of this study are two English teachers who taught in grades 1A and 1B at Genta Saraswati Bilingual and Montessori School Bali. This research uses a qualitative method by using observation checklists and conducting interviews with the two teachers. The results showed that the two teachers did not experience serious challenges. The challenges experienced by teachers, such as time management, managing groups in making projects, and students who have lack of confidencs in presenting the result of the project. To overcome the challenges teachers in both grades have their own strategies for overcoming the difficulties they experience and strategies for teaching in class because both teachers already understand the characteristics of students and the appropriate strategies to use in class.